AN ANALYSIS OF ENGLISH-SPEAKING ANXIETY ENCOUNTERED BY STUDENTS IN ENGLISH EDUCATION DEPARTMENT - ELLI MARLIANA; YAYU YAYU (Universitas Mahasaraswati K. Mataram, 2023)
This research focused on analyzing English speaking anxiety that experienced by the second semester students of English education department at STKIP Paracendekia NW Sumbawa. Through a descriptive qualitative method, this research aimed to find out factors that cause English speaking anxiety, students’ efforts to overcome their English-speaking anxiety, and category of anxiety that is experienced in the students. The respondents who are selected purposively in this research consisted of ten students from class A and B second semester in English Education Department at STKIP Paracendekia NW Sumbawa. This research used interview and observation techniques to collect the data which later the data analyzed using three techniques: data reduction, data display and drawing conclusion or verification. The result of this research reveals the factors that cause English speaking anxiety are lack of vocabulary, low English proficiency, lack of practice, lack of preparation and fear of making mistakes and being laughed at. In addition, the strategies used by the students to overcome their English-speaking anxiety are preparation, relaxation and positive thinking. Furthermore, the category of anxiety experienced by the students in this research is state anxiety.